Penerapan Model Cooperative Integrated Reading And Composition Dengan Media Komik Dalam Meningkatkan Kemampuan Membaca Peserta Didik Kelas Iv Sd Negeri 1 Langgikima - Ratnasari Ratnasari; Ashari Usman; La Sisi (Jurnal Sultra Elementary School, 2021)
This study aims to determine the improvement of reading skills after applying the Cooperative Integrated Reading and Composition (CIRC) model assisted by comic media for fourth-grade students of SD Negeri 1 Langgikima. This research is a Classroom Action Research (CAR). The subjects of this study were 25 fourth-grade students of SD Negeri 1 Langgikima. The results showed an improvement in students’ reading skills, where in the first cycle, 18 out of 25 students achieved mastery with a success rate of 72%, while in the second cycle, 23 out of 25 students achieved mastery with a success rate of 92%. These findings indicate that the application of the CIRC model with the help of comic media can effectively improve students’ reading skills.